AN EMPIRICAL STUDY ON CONSUMER BUYING BEHAVIOUR OF SELECTED HOSIERY PRODUCTS - Agarwal, Mukesh V (PEOPLE: International Journal of Social Sciences, 2019)
Consumer behaviour tells us what the needs of consumers are. It identifies simple but powerful facts about buying behaviour -who buys, what they buy, and how do they buy. The results give us amazing insights into what customer's thinking process is and how they differ across different background variables. Demographic and higher disposable income in urban buyers has created a paradigm shift in buying behaviour. Ever increasing competition and availability of various options has made marketers understand various factors which are influencing the demand for Hosiery products. The research paper attempts to highlight some of the aspects affecting the consumer buying behaviour of selected hosiery products. Consumer personal traits and perception, personality and motivation are some factors whereas external influencing sources are family social cultural and regional factors. There are three steps viz. before buying, during making the purchase decision and after buying. Before buying step may be affected by brands, social status individual educational qualification, monthly income etc. During making the purchase may be impacted by aspects such as price, packaging review, value price and comparison with other brands, etc. Marketer should be vice in selecting advertising instrument as it has a lasting impact of customer mind creating brand awareness and emotional touch are key factors. Repeated purchase of same brand is brand loyalty whereas switch over might be indication for a change in behaviour of the consumer.